Paola Santiago and the forest of nightmares - Mejia, Tehlor Kay (Paola Santiago, 2021)
Months after confronting the legendary La Llorona, Paola starts dreaming again, this time about fantasmas that are stalking her and someone who might be even more dangerous--her estranged father.